THE ROLE OF THE INDONESIAN YOUTH NATIONAL COMMITTEE (KNPI) IN BUILDING YOUTH CHARACTER - Idrus Maha; Tarmizi Tarmizi; Rudjiman Rudjiman; Ayu Anggraini Tambunan (Sekolah Tinggi Pariwisata Mataram, 2023)
The purpose of this study is to examine the influence of the Indonesian Youth National Committee (KNPI) in shaping the character of Dairi Regency's youth. This study focuses on the role performed by the Indonesian Young National Committee (KNPI) in implementing its work program to enhance youth character in the Dairi Regency. Youth development may be accomplished via a variety of ways, including character education, since character education is one of the keys to national advancement. Character education is a method of character development that may be included into any educational program. This study employs a descriptive technique with a qualitative approach. This research utilizes both primary and secondary data sources, including the Dairi Regency Youth Sports and Tourism Service, the Dairi KNPI, the Youth and Sports Office, and the Dairi Regency Central Bureau of Statistics. The results show that the KNPI youth have a role in building youth character in Dairi Regency and there are also obstacles to the Dairi Regency KNPI DPD in building youth character.